Aflatoxins in Food and Feed: An Overview on Prevalence, Detection and Control Strategies - Mahato, Dipendra K.; Lee, Kyung Eun; Kamle, Madhu; Devi, Sheetal; Dewangan, Krishna N.; Kumar, Pradeep; Kang, Sang G. (Frontiers in Microbiology, 2019)
Aflatoxins produced by the Aspergillus species are highly toxic, carcinogenic, and cause severe contamination to the food sources leading to serious health consequences. Contaminations by aflatoxins have been reported in food and feed such as groundnuts, millet, sesame seeds, maize, wheat, rice, fig, spices and cocoa because of fungal infection during pre- and post-harvest condition. Commercial products like peanut butter, cooking oil and cosmetics are also reported to be contaminated by aflatoxins besides the food products. Even the low concentration of aflatoxins is hazardous for human and livestock. The identification and quantification of aflatoxins in food and feedstuff is a major challenge to guarantee food safety. Therefore, developing feasible, sensitive and robust analytical methods is paramount for the identification and quantification of aflatoxins present in low concentration in food and feedstuff. There are various chromatographic and sensor-based methods used for the detection of aflatoxins. The current review insight the sources of contamination, occurrence, detection techniques, masked mycotoxin along with management’s strategies of aflatoxins to ensure food safety and security.